Pengembangan Sistem Keamanan Pintu Menggunakan Metode Prototype Berbasis RFID dan Keypad 4x4 dengan Arduino Nano - Alfonsius, Eric; Ruitan, Anna Stefanie; Liuw, Daniel (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2024)
Security of room access is one of the important aspects in maintaining privacy and asset protection. Traditional mechanical key systems have limitations because they only provide one layer of security, which is vulnerable to theft and key duplication. Along with the development of technology, especially in the fields of Electronics and Informatics, various innovations have been presented to improve security, one of which is RFID (Radio Frequency Identification) technology. RFID allows object identification without direct contact, but its weakness is that it is still limited to one layer of security. This study aims to develop a layered security system using Arduino Nano that combines RFID technology and 4x4 Keypad. This system is designed to ensure that only users who have the correct tag card and access code can open the door. With a combination of RFID for identification and Keypad for additional verification, this system is expected to significantly improve room access security. The prototype developed offers an innovative solution in the door security system, so that it can be applied in various places that require extra protection such as offices, hotels, and other facilities. This is evidenced by the results of the blackbox test which reached 100% from several test results from each test item.